3D Visualization Design for WebVR-based Job Fair Information System - Yuyun Khairunisa; Ratu Verlaili; Fiki Abdul Rahman (ABEC Indonesia, 2022)
Virtual reality (VR) is a technology that displays a virtual world at the same time as the real environment. Several studies related to the application of virtual reality technology include motivation, experience and understanding. One of the technologies used in this research is the development of VR on the web or called Web VR. This framework can be embedded in the job market information system (SIMJOF). Web Virtual Reality can be patented in a web environment and can interact with queries to produce a more dynamic web. Web VR is an implementation of Virtual Reality on a website without using additional technology such as VR glasses. Web VR implementation using A-Frame technology which is a web framework for building virtual reality experiences with html and entity components. In this study, Virtual Reality is used to describe the state of the job market in the Polymedia virtual space. Users will be invited around to visit the boot of each company. In addition, users can access information related to company profiles and job listings. 3D animation created using Blender software. 3D models are created to depict the real job market environment. The Job Fair was held at the Polimedia Hall Tower E, the State Polytechnic of Creative Media. The job fair environment consists of the building environment, stage environment, stand environment, people, and attributes. The virtual tour is linked to a navigation bar listed in the submenu of the website. Functional testing of the application using alpha testing shows that the functions on the virtual tour (virtual reality) menu can work well (Fulfilled/T).